Face-veiled women in contemporary Indonesia - Nisa, Eva F., author.
1 online resource.
Keywords: "Although face-veiling is new and unusual in Indonesia, an increasing number of women are choosing to wear the cadar, that is the full face-veil. This book, based on extensive original research, explores why Muslim women choose to wear the cadar and what the consequences are. It outlines how these women belong to two Islamist revivalist movements- the Salafi groups and the Tablighi Jama'at, shows how the practice of Islam in Indonesia continues to shift over time, and demonstrates that women are key actors in that process"--